The role of three-phase 99mTc-MDP bone scintigraphy in the diagnosis of periprosthetic joint infection of the hip and knee - Pucar, Dragan M; Janković, Zoran; Baščarević, Zoran; Starčević, Srdjan; Čizmić, Milica; Radulović, Marija (Vojnosanitetski pregled, 2017)
Background/Aim. In the last five decades primary hip and knee arthroplasty is the most common and effective surgical intervention worldwide. Infection, although unfrequented, is the most serious complication. Nuclear medicine imaging, not affected by metallic hardware, is the current imaging modality of choice for the evaluation of suspected joint replacement infection. The aim of this study was to estimate the diagnostic accuracy of three phase 99m technetium methylene diphosphonate (99mTc-MDP) bone scintigraphy in periprosthetic hip and knee joint infection. Methods. Inclusion criteria of patients in the study were suspected knee or hip periprosthetic joint infections. In this study, we examined 45 patients (14 men and 31 women) with 39 hip and 24 knee prosthesis (total 63). In all patients, three-phase bone scintigraphy was performed after intravenous application of 555 MBq of 99mTc-MDP. The final confirmation of infection was microbiological or pathohistology finding. Results. Infection was confirmed in 29 prosthetic joints, in 13 (44.8%) knee and 16 (55.2%) hip joints while there was no infection in 34 prosthetic joints. The connection of different modalities of negative and positive findings 99mTc-MDP three-phase bone scintigraphy with the final confirmation of infection showed a high statistical significance (p < 0.001). Three phase bone scintigraphy showed a high sensitivity of 90% but a modest specificity of 69.7% in the detection of periprosthetic infection with the diagnostic accuracy of 79%. The calculated positive predictive value was 73% but the negative predictive value was high 89%. Our results of three-phase bone scintigraphy with calculated sensitivity, specificity and diagnostic accuracy of 79% are in consent with the majority of published studies, or even slightly better. Conclusion. Bone scintigraphy is sensitive in the diagnosis of periprosthetic infection but insufficiently specific. In the detection of periprosthetic infections three-phase bone scan can be used as a diagnostic method of the first line only aimed at its exclusion. The only reasonable use of bone scintigraphy is in combination with other radionuclide methods with high specificity.